American Militarism 1970 : a dialogue on the distortion of our national priorities and the need to reassert control over the defense establishment. - Knoll, Erwin; Fulbright, J. William; McFadden, Judith Nies (New York US : The Viking Press, 1969)
Obra de teatro que ilustra la situación conflictiva en El Salvador en la década de los setenta.
Keywords: ESTADOS UNIDOS DE AMÉRICA; MILITARISMO; SEGURIDAD CIUDADANA; POLÍTICA EXTERIOR